2018
DOI: 10.3892/ol.2018.8953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in cervical cancer by bioinformatics analysis

Abstract: Cervical cancer is the most common gynecological malignancy. In recent years, the incidence of cervical cancer has had a younger trend. Cervical cancer morbidity and mortality rates have been significantly reduced due to recent decades of cervical cytology screening leading to the early detection and treatment of cervical cancer and precancerous lesions. There are a number of methods used to treat cervical cancer and improve the survival rate. However, the prevalence and recurrence rates of cervical cancer are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…As a result of the limited therapeutic schemes, CC is still a major threat to women's health. Thus, further investigations of the molecular mechanisms are necessary …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the limited therapeutic schemes, CC is still a major threat to women's health. Thus, further investigations of the molecular mechanisms are necessary …”
Section: Introductionmentioning
confidence: 99%
“…Thus, further investigations of the molecular mechanisms are necessary. 6 Increasing studies focus on the function and underlying mechanism of long non-coding RNA (lncRNA) in human tumors. [7][8][9] As a member of non-coding RNA (ncRNA) family, lncRNA is defined as the RNA transcripts with a length > 200 nucleotides, which is differentiated from other ncRNAs, such as microRNA and transfer RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the detection of drug resistance mainly relies on Sanger automated sequencing and second-generation sequencing (NGS), and NGS is an emerging technology with great potential in data analysis and data integrity [78]. Of note, international guidelines recommend that RAS present in >15% of sequences are believed clinically significant and should be taken into serious consideration in the selection of treatment regimen [102,103].Conversely, in a RAS study based on massively parallel, they reported that presence of baseline RASs even much less than 15% of HCV sequences is also associated with treatment failure in two HCV G1a-infected patients treated with ledipasvir (LED)+ sofosbuvir (SOF) [67,[104][105][106].…”
Section: Drug Resistancementioning
confidence: 99%
“…Five hundred and thirty-three patients were randomly assigned to the training set (n = 350) and validation set (n = 183). The GEO (http://www.ncbi.nlm.nih.gov/geo/) database, a comprehensive library of gene expression, is a free public database (23)(24)(25)(26). Using "ccRCC" as the search term, relevant data sets were screened from the GEO database.…”
Section: Patient Datamentioning
confidence: 99%